Retail Out-of-stocks in the Context of Centralized and Direct Delivery - Milićević, Nikola; Grubor, Aleksandar; Đokić, Nenad; Avlijaš, Goran (Promet - Traffic&Transportation, 2018)
The delivery of the right product, at the right time to the retail store, only seems to be an easy process. The smallest problem can cause the out-of-stock (OOS) situation, which may prevent customers to buy products they were looking for. Consequently, it affects retailers and their suppliers through potential operational inefficiencies, sale losses and eventually the losses of their loyal customers. Starting from these problems, by using the data of a large Serbian retailer, this paper analyses out-of-stocks in the context of two alternative delivery systems, centralized and direct. For calculating OOS rates the perpetual inventory aggregation metrics was used, while the occurrence of out-of-stocks was modelled by the application of probit regression analysis. The results have shown that delivery system has a significant impact on the probability of a stock-out, indicating potential problems in the centralized system. In addition, the analysis included certain product and store characteristics that also significantly affect the average probability of stock-outs.